A Socio-Legal Study of Health Problem and Prospects in District Udham Singh Nagar, Rudarpur Uttarakhand Brief History of the District: Exploring the Impact of Health Issues on District Udham Singh Nagar in Uttarakhand (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Udham Singh Nagar is situated in Tarai area of the state and it is the third crowded District in the State of Uttarakhand. Rudrapur is the locale Headquarters of Udham Singh Nagar, already this zone was a piece of Nanital area. This territory was comprised into an autonomous locale in the year 1995, preceding that, it was the piece of area Nainital. This isolated piece of Nainital locale was named after Saheed Udham Singh, one of the extraordinary opportunity warriors, who vindicated the Jallian Walla Bagh slaughter submitted by General Dyer in the British India. Udham Singh Nagar is additionally called the Entryway to Kumaon Hills.